Pengaruh Pemberian Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea Batatas (L.) Lam) terhadap Kadar Kolesterol Ldl Tikus Hiperkolesterolemia - Siti Fatimah; Yuliana Prasetyaningsih (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Hypercholesterolemia is still a health problem today because it is associated with the onset of cardiovascular disorders with various complications. High cholesterol levels carried by the blood will accumulate in the arteries that cause atherosclerosis. Blood clots and blockage of blood vessels can result in the stroke or heart attack. Flavonoids that are found in purple sweet potato leaves are quercetin. Quercetin has antioxidant effects that can improve blood vessel endothelial function, reduce LDL sensitivity to free radical effects, and reduce blood lipid levels. This study aims to determine the effect of ethanol extract of purple sweet potato leaves on LDL cholesterol level of hypercholesterolemia rat. The experiment was conducted experimentally using 2 groups of Wistar rats (each group consisting of 5 tails), namely the control group and the treatment group. Induction of hypercholesterolemia was performed with a high-fat diet for 7 days. The purple sweet potato ethanol extract was administered sonde in the treatment group with a quercetin dose of 2 mg /kg/day for 14 days and the measurement of LDL cholesterol was performed on days 10 and 24 by the CHOD-PAP method. Data were analyzed by Paired t-test. The results showed that LDL cholesterol level in the treatment group showed that 5 mice had decreased, the mean decrease of 32,49 mg/dl while control group 3 decreasing, mean 0,65 mg /dl. There was a significant difference (p <0.05) on changes in LDL cholesterol levels in the treatment group. Provision of purple sweet potato ethanol extract with quercetin dose of 2 mg/kg for 14 days can decrease LDL cholesterol level of hypercholesterolemia rat. From the results of this study is expected to optimize the utilization of purple sweet potato leaves (Ipomoea batatas (L.) Lam) as a drug for lowering LDL cholesterol.